An Exploration of a Historically Marginalized Student’s Experience with Portfolios - Jaramillo Martinez, Leslie (Tufts Archival Research Center, 2023)
This thesis discusses my experiences and outcomes of building a portfolio as a historically marginalized student.; Thesis (B.S.M.E.)--Tufts University, 2023.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Briana Bouchard.; Committee: Kristen Wendell, Greses Pérez.